Recommendations for minimum information for publication of experimental pathology data: MINPEPA guidelines. Issue 2 (28th November 2015) - Scudamore, Cheryl L; Soilleux, Elizabeth J; Karp, Natasha A; Smith, Ken; Poulsom, Richard; Herrington, C Simon; Day, Michael J; Brayton, Cory F; Bolon, Brad; Whitelaw, Bruce; White, Eric S; Everitt, Jeffrey I; et al.
Abstract: Animal models are essential research tools in modern biomedical research, but there are concerns about their lack of reproducibility and the failure of animal data to translate into advances in human medical therapy. A major factor in improving experimental reproducibility is thorough communication of research methodologies. The recently published ARRIVE guidelines outline basic information that should be provided when reporting animal studies. This paper builds on ARRIVE by providing the minimum information needed in reports to allow proper assessment of pathology data gathered from animal tissues. This guidance covers aspects of experimental design, technical procedures, data gathering, analysis, and presentation that are potential sources of variation when creating morphological, immunohistochemical (IHC) or in situ hybridization (ISH) datasets. This reporting framework will maximize the likelihood that pathology data derived from animal experiments can be reproduced by ensuring that sufficient information is available to allow for replication of the methods and facilitate inter‐study comparison by identifying potential interpretative confounders. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.